APPEARANCE OF BROILERS GIVEN LIGNOCELLULOLYTIC PROBIOTIC FERMENTED FEED - A D. D., Mario; Mudita, I M.; Siti, N. W. (Jurnal Peternakan Tropika; Vol 10 No 3 (2022): Vol. 10 No. 3 Tahun 2022; September - December, 2022)
This study aimed to determine the effect of fermented rations of lignocellulolytic probiotic bacteria on the appearance of broilers. The research was conducted at Farm Sesetan, Faculty of Animal Husbandry, Udayana University, Denpasar, which took place from May 25 to June 29 2021. The design used was a completely randomized design (CRD). Each experimental unit was filled with three broilers with homogeneous body weights ranging from 43.96 g ± 3.02. The five treatments were broilers fed commercial rations (RK), fermented ration without bacterial inoculum (RF0), broilers fed fermented rations with 5% Bacillus subtilis BR4LG (RF1) inoculum, fermented ration with Bacillus sp. 5% BT3CL (RF2), and fermented rations with Bacillus sp. BT8XY as much as 5% (RF3). The variables observed were ration consumption, drinking water consumption, initial and final weight, body weight gain, and feed conversion ratio. The results showed that the RF1, RF2, and RF3 treatments resulted in drinking water consumption, weight gain, and final weight which were significantly (P<0.05) higher than RF0, but compared to the RK treatment, RF1, RF2, and RF3 treatments resulted in ration consumption, drinking water consumption, weight gain, and final weight were significantly (P<0.05) lower. Based on the results of the study, it can be said that the fermented ration of lignocellulolytic probiotic bacteria was able to increase water consumption, weight gain, final weight, and improve the FCR of broilers compared to (RF0), but the performance of the fermented ration of lignocellulolytic probiotics prepared was still unable to compete appearance of (RK). Keywords: Broiler, Appearance, Probiotics, Lignocellulolytics